2013
DOI: 10.12968/bjcn.2013.18.6.275
|View full text |Cite
|
Sign up to set email alerts
|

COPD in primary care settings in Ireland: stories from usual care

Abstract: The aim of the PRINCE study was to determine the effectiveness of a structured education pulmonary rehabilitation programme for those living with COPD in primary care in Ireland. This qualitative element of the larger PRINCE trial aims to describe the constituents of 'usual care' for patients allocated to the control arm of the study. A descriptive qualitative study was used to explore the constituents of usual care. A convenience sample of participants (n=20) allocated to the usual care group were interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Patients failed to understand terminology, conflating COPD with asthma, did not understanding the progressive/incurable nature of COPD, and were confused regarding exercises and how to recognise and respond to exacerbations. 33 , 34 , 42 45 , 55 , 56 Family/carers could often fill this gap by taking responsibility for asking questions and implementing information. 29 , 59 Lack of understanding or confusion could lead to frustration and have implications for patient’s confidence in undertaking self-management activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients failed to understand terminology, conflating COPD with asthma, did not understanding the progressive/incurable nature of COPD, and were confused regarding exercises and how to recognise and respond to exacerbations. 33 , 34 , 42 45 , 55 , 56 Family/carers could often fill this gap by taking responsibility for asking questions and implementing information. 29 , 59 Lack of understanding or confusion could lead to frustration and have implications for patient’s confidence in undertaking self-management activities.…”
Section: Resultsmentioning
confidence: 99%
“… 33 , 38 , 45 However, eight studies reported that patients had either received limited or no information from practitioners. 33 , 38 , 43 45 , 55 , 56 , 58 Patients felt frustration due to conflicting information received from different practitioners and external sources, a lack of opportunity to ask questions within consultations, and medicine being prioritised over lifestyle concerns. Conversely, practitioners were concerned about patients’ confidence, literacy, health literacy, and recall.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding information part, one study finds that the patients have “expert” knowledge, and that they know what to do in the case of exacerbations 22. Other studies, however, show that the patients do want more information about COPD early in the process, preferably at the time of diagnosis,23 and that patients with moderate COPD lack knowledge of the disease 14,2426. Because COPD is a progressive disease, the need for information and behavior change counseling can vary over time.…”
Section: Discussionmentioning
confidence: 99%
“… 32 General practice nurses described key factors that affected self-management as poor knowledge of COPD and aspects of self-management amongst nurses, competing demands, poor team working and lack of multidisciplinary support. 43 , 44 Primary care doctors, nurses and allied health practitioners working across primary, community and secondary settings have also identified barriers relating to poor understanding and awareness of COPD (e.g., delineating between COPD and asthma diagnosis), limited time, lack of awareness of educational and learning needs and expectations about patients’ self-management capabilities. 22 , 26 Similar findings have also been reported in studies in other LTCs.…”
Section: Discussionmentioning
confidence: 99%